Experimental archaeology : making, understanding, story-telling : proceedings of a workshop in experimental archaeology : Irish Institute of Hellenic Studies at Athens with UCD Centre for Experimental Archaeology and Material Culture, Dublin, Athens 14th-15th October 2017 - Souyoudzoglou-Haywood, Christina; O'Sullivan, Aidan (Archaeopress Archaeology, 2019)
In this text, based on the proceedings of a two-day workshop on experimental archaeology at the Irish Institute of Hellenic Studies at Athens in 2017, scholars, artists and craftspeople explore how people in the past made things, used and discarded them, from prehistory to the Middle Ages.